2003
DOI: 10.1016/s0014-5793(03)00362-4
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and p43 binding of the p38 leucine zipper motif: coiled‐coil interactions mediate the association between p38 and p43

Abstract: p38, which has been suggested to be a sca¡old protein for the assembly of a macromolecular tRNA synthetase complex, contains a leucine zipper-like motif. To understand the importance of the leucine zipper-like motif of p38 (p38LZ) in macromolecular assembly, the p38LZ solution structure was investigated by circular dichroism and nuclear magnetic resonance spectroscopy. The solution structure of p38LZ showed an amphipathic K K-helical structure and characteristics similar to a coiled-coil motif. The protein^pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…1A) and real-ime RT-PCR (supplemental Table 1 The Effect of Depletion of AIMPs-AIMP2 has been shown by in vivo analysis (26) to be critical for the integrity of the whole complex and the stability of its components. It interacts with AIMP1 via a coiled-coil interaction (27). We found that depletion of any one of the three AIMPs greatly affected the levels of the others (Fig.…”
Section: Systematic Depletion Of Components Of the Multi-arsmentioning
confidence: 70%
“…1A) and real-ime RT-PCR (supplemental Table 1 The Effect of Depletion of AIMPs-AIMP2 has been shown by in vivo analysis (26) to be critical for the integrity of the whole complex and the stability of its components. It interacts with AIMP1 via a coiled-coil interaction (27). We found that depletion of any one of the three AIMPs greatly affected the levels of the others (Fig.…”
Section: Systematic Depletion Of Components Of the Multi-arsmentioning
confidence: 70%
“…p38 contains two functional domains, such as leucine zipper domain at its N terminus, which is involved in macromolecular assembly of ARSs (Quevillon et al, 1999;Ahn et al, 2003) and a GST-homology domain at the C terminus. We did not observe an interaction with parkin in these functional domains; instead, mapping studies indicate that parkin mainly interacts with the 82-162 domain of p38.…”
Section: Discussionmentioning
confidence: 99%
“…The N terminus contains a coiled-coil structure, which may play an important role in protein-protein interaction. Furthermore, the N terminus of pro-EMAP II has been reported to interact with its own N terminus, p38, RARS, QARS, and the leucine zipper of AIMP2 (21,23,24,38), suggesting that the N terminus may mediate the association of pro-EMAP II to MSC. However, the structure and function of N terminus of pro-EMAP II remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellularly, pro-EMAP II directly interacts with other components of the MSC, such as p38, arginyl-tRNA synthetase (RARS), and glutaminyl-tRNA synthetase (QARS) (21)(22)(23)(24). Such an interaction plays an important role in the assembly and function of the MSC.…”
mentioning
confidence: 99%